The dynamic process of pro-market reforms and foreign affiliate performance: When to seek local, subnational, or global help? - Chan, Christine M.; Du, Jialin (Journal of International Business Studies, 2021)
Little is known about how the dynamic process of pro-market reforms influences the performance of foreign affiliates in emerging economies and how multinational enterprises (MNEs) can deal with such a dynamic process. This study disentangles the dynamic process of pro-market reforms into three dimensions – speed, (un)predictability, and (un)synchronization – and argues that the performance of foreign affiliates suffers when pro-market reforms are slow, unpredictable, and unsynchronized. To mitigate the detrimental impacts of the three distinctive dimensions of pro-market reforms, MNEs can deploy strategies that allow their foreign affiliates to seek local help from other strongly embedded “central” organizations, subnational help from sister affiliates in other subnational regions of the same host country, and global help from parent firms. To test these arguments, this study performs a 10-year longitudinal analysis of 79,763 foreign affiliates operating in China. The results provide evidence that seeking local help is effective in mitigating the negative effect of slow pro-market reforms on foreign affiliate performance, but has no effect on the unpredictability of pro-market reforms. In addition, subnational help is as effective as global help in mitigating the negative effect of unsynchronized pro-market reforms on foreign affiliate performance.